Enhancing Students’ Schematic Construction of Authentic-Based Generic Discoursal Structuring - Nour el Houda KHELOUFI (Revue des Sciences Humaines, 2015)
English language learners face many problems when processing the information especially in authentic contexts.  This issue carries a great importance in pedagogy as a crucial point to have discourse competence.  In this respect, this article reports on an experimental design which was conducted with 120 informants from the department of English (University of Mentouri Brothers-Constantine) divided into control and experimental groups in which learners of both groups were pre-tested and post-tested. The experiment checks the hypothetical criterion of testing the effect of the communicative nature of the authentic side of language on learners’ schematic knowledge.  Hence, it examines the aspect of enhancing learners’ discourse competence via a rhetorically authentic contextualisation of language. This is more particularly entailed in the different contextual factors as guidelines for the authenticity of communication. The comparison of the pre-test and the post-test results reveals a remarkable enhancement in the students’ schematic competence vis-à-vis the authentic use of language.